Strategic management of records and risks for the sustainability of organizations / Azman Mat Isa, Raja Abdullah Yaacob and Nordiana Mohd Nordin - Yaacob, Raja Abdullah; Mohd Nordin, Nordiana (Faculty of Information Management, 2013)
The sustainability of an organization relies on its financial stability and its ability to demonstrate considerable transparency and accountability. Records management has a significant role in providing evidence for decision-making as well as for demonstrating transparency and accountability. Implementing records management would be costly in the absence of risk management. Unfortunately, the role of records management is hardly recognized. This research attempts to investigate the essence of records management in underpinning good governance and accountability processes as well as to identify the relationship between risk management and records management. This research adopts case study method, using interviews, observation and document analysis for data gathering. It is discovered that an integrated records management system is essential in underpinning critical governance and accountability processes such as internal and external audit, compliance, risk management and decision making.